The Potential Use of Red Ginger (Zingiber officinale Roscoe) Dregs as Analgesic - Febriani, Yessi; Riasari, Hesti; Winingsih, Wiwin; Aulifa, Diah Lia; Permatasari, Ayu (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Red ginger (Zingiber officinale Roscoe) had been used as excipient in jamu for most people in Indo- nesia. Based on recent research, ethanol extract of red ginger had analgesics activity. The purpose of this research to determine analgesic activity content in water extract of the fresh and dry red ginger and ethanol extract of fresh and dry of red ginger dregs. Fresh and dry of red ginger extracted using decoc- tion method, and the dregs of fresh and dry red ginger extracted using soxhletation method in ethanol 96% at 400C. Red ginger water extract and red ginger dregs extract had been examined for analgesic by witkin method. The results showed, fresh and dry red ginger water extract had analgesic activity for 25 minutes but the activity reduced in 30 minutes. Fresh and dry red ginger dregs ethanol extract still had analgesic activity until 30 minutes. TLC chromatogram was sprayed with FeCl3 and formed two spots with grey colour for both extracts. After sprayed with vanillin sulfate, it formed violet and blue spots from both extracts. From the retention factor (Rf) , possibility shogaol and gingerol contained in extract that have analgesic activity. Key words: Analgesic, dregs, phenolic, red ginger (Zingiber o cinale Roscoe), Witkin method.